Border Trickery and Dog Bones:: A Conversation with Thomas King - Andrews, Jennifer (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 1999)
Thomas King discusses whether or not he thinks Green Grass, Running Water is a Canadian novel, a Native novel, or both, the borders that cut between races, and the discomfort that the insider/outsider phenomenon creates for certain groups of readers. He also articulates his resistance to being labelled a comic writer and makes comparisons between Green Grass and Truth and Bright Water. He later discusses his radio show, Dead Dog Café, and his photography.